MODEL PENEMPATAN PARIT CACING PADA BUDIDAYA KELAPA DALAM (Cocos nucifera L.) DI LAHAN PASANG SURUT - Taufik, Muhammad; Hartawan, Rudi (Jurnal Media Pertanian, 2021)
Cultivation techniques in tidal land are very important to support the growth and productivity of Tall Coconut. The purpose of this study was to determine the growth, production, and productivity of Tall Coconut in several field drain models. This research was conducted from December 2019 to January 2020 in the tidal area of Tanjung Api-Api Village, Sebrang District, Tungkal IV City, Tanjung Jabung Barat Regency. This research was conducted using a survey method on farmers' gardens and unformatted trials. There are 4 models of field drain, namely model 1, model 2, model 3, model 4 and without field drain. The variables observed were soil pH and water quality, plant physics, fruit physics, and agronomic action. The research data were analyzed by statistic. The results showed that soil pH and water chemical quality showed that field drain Â model 1 gave the best value with soil pH, water pH, iron, sulfur, and sodium content of 5.2, 5.4, 85 ppm, 119 mL-1, and 270 mL-1 respectively. The highest plant growth, production and productivity were found in plants with field drain model 2. Data on stem circumference, number of midribs, and number of bunches of knees were 81.10 cm, 25.8 strands, and 14.2 bunches respectively. Data of fruit weight, fruit circumference, coir thickness, weight of fruit without coir and productivity were 1,800 g, 59.2 cm, 3.2 cm, 1,003 kg, and 1,168 items hectar-1 year-1, respectively. Agronomic measures include controlling weeds with herbicides and generally without fertilizing. Field drain aims to facilitate coconut harvesting and to avoid the toxic effects of peat soil.